Dynamic hospital competition under rationing by waiting times - Sá, Luís Carlos Sousa (2018)
We develop a dynamic model of hospital competition where (i) waiting times increase if demand exceeds supply; (ii) patients differ in their evaluation of health bene ts and choose a hospital based on waiting times; and (iii) there are penalties for providers with long waits. We show that, if penalties are linear in waiting times, a more competitive dynamic environment does not affect waiting times. If penalties are instead non-linear, we find that waiting times are longer under the more competitive environment. The latter result is derived by calibrating the model with waiting times and elasticities observed in the English NHS for a common treatment (cataract surgery), which also shows that the difference between waiting times under the two solution concepts is quantitatively small. Policies that facilitate patient choice, an alternative measure of competition, also lead to higher steady-state waiting times, and tougher penalties exacerbate the negative effect of choice policies.